A dataset of individual wet weights of benthic macroinvertebrates - Allison R. Hrycik; Lyubov E. Burlakova; Alexander Y. Karatayev; Susan E. Daniel; Ronald Dermott; Morgan Tarbell; Elizabeth K. Hinchey (Limnology and Oceanography Letters)
Abstract Biomass estimates are crucial for modeling and understanding energy flow through ecosystems. Many modeling frameworks rely on published body weights of organisms to convert density estimates to biomass. However, published body weight data are limited to few taxa in a limited number of systems. Here we present mean individual weights for common benthic macroinvertebrates of the Laurentian Great Lakes from over 2000 benthic samples and 8 yr of data collection. We also compiled wet to dry weight conversions to facilitate data reuse for researchers interested in dry weight. We compared our benthic invertebrate weights to other lakes, demonstrating when weight measurements may be applied outside the Great Lakes. Sensitivity analyses supported the robustness of our calculations. Our dataset is applicable to food web energy flow models, calculation of secondary production, interpretation of trophic markers, and for understanding how biomass distribution varies by benthic invertebrate species in the Great Lakes.